Depression in elderly in Peru: geospatial distribution and associated factors according to ENDES 2018 - 2020 - Martina Chávez, Martha (2022)
Introduction. Depression in the elderly population is a public health issue and few studies analyze its distribution according to geographic areas. Objectives. To describe the geospatial distribution and associated factors of depressive syndrome (DS) in Peruvian older adults according to ENDES 2018 to 2020. Methods. Cross-sectional and analytical study based on data from national surveys, which used the PHQ-9 scale to measure DS. The analysis used Pearson’s Chi square test and multivariate logistic regression and OR with p < 0,05. Results.  The prevalence of DS in 2018 was 12.9%; 13.3% in 2019 and 10.8% in 2020. The factors associated with DS were: being a woman, living in poverty, having secondary education, residing in rural areas, coming from the mountains and jungle, living alone and being 75 years of age or older. The geospatial analysis shows that the SD is concentrated in five departments: the coast (Lima, La Libertad, Piura) and the southern highlands (Puno, Arequipa).  Conclusions. Public policies aimed at reducing DS should focus on women, older than 75 years and those who live in rural areas and fundamentally those who live in the departments identified as having the highest prevalence.